2024
DOI: 10.1186/s12884-023-06206-z
|View full text |Cite
|
Sign up to set email alerts
|

Mobile health apps for pregnant women usability and quality rating scales: a systematic review

Mohammad Reza Mazaheri Habibi,
Fateme Moghbeli,
Mostafa Langarizadeh
et al.

Abstract: Objective This study is to identify the apps used by pregnant women during the technology era and to choose the best app from the point of view of pregnant women and experts. Methods The article is a research article that uses PRISMA flowchart. Given that there are many apps in the field of pregnancy and due to technological advances, the articles of the last 13 years that have been scientifically published in the databases of Google Scholar, PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Among the other reasons for the increase in cesarean deliveries are women’s negative attitude towards their previous birth experiences, anxiety and depression, and their difficult social and economic conditions. There are various studies in this field, which have shown the effect of training during pregnancy on the readiness for childbirth [ 1 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the other reasons for the increase in cesarean deliveries are women’s negative attitude towards their previous birth experiences, anxiety and depression, and their difficult social and economic conditions. There are various studies in this field, which have shown the effect of training during pregnancy on the readiness for childbirth [ 1 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%